Economic Theory and the Meaning of Competition - McNulty, Paul J. (Quarterly Journal of Economics, 1968)
Introduction, 639. — I. Meaning of competition, 639. — II. Evolution of the concept of competition, 643. — III. Weaknesses of the classical concept of competition, 650. — IV. Conclusion, 656.